INTERACTION OF PROSTAGLANDIN E(2) (PGE(2)) WITH NORADRENALINE AND ITS ANTAGONISTS IN THE ISOLATED MESENTERIC ARTERY OF RAT (1980)
The effect of PGE(2), PGF(2a) and PGI(2) on constriction induced by different mechanisms was studied in the isolated rat mesenteric artery as described by McGregor (1965) Vasoconstriction was induced by mechanisms involving dif modes of calcium utilization viz: (i) Pharmacomechanical pathway by low doses of the adrenergic neurotransmitter, noradrenaline acting at α- receptor; (ii) electromechanical pathway by high potassium and (iii) agents which facilitate Ca(2t) influx e.g. A23187. The prostaglandins potentiated the vasoconstrictor effect of NA. Potentiation factors calculated from different doses of the prostaglandins showed the effects of the prostaglandins to be dose - dependent and PGE(2) to be significantly more potent (P>0.005) than PGF(2a) and PGI(2). The prostaglandins failed to potentiate high potassium - induced vasoconstriction. PGE(2) also failed to potentiate NA if the vasoconstrictor effects were evoked in Ca(2+) - free Krebs solution; but the degree of potentiation increased with increase in the concentration of Ca(2+) ions in the perfusion fluid. This result suggested strongly that the potentiation was associated with external calcium. Evidence is presented to show that potentiation was not prejunctional since cocaine, bretylium and reserpine pretreatment did not materially alter the effect of PGE(2). It was concluded that prostaglandins potentiated NA vasoconstriction by facilitating Ca(2a) influx. The mechanism of this facilitation is discussed. NA vasoconstriction was competitively antagonised by adrenoceptor antagonists-phentolamine, tolazoline, yohimbine and phenoxybenzamine (in low concentrations). The blockade caused by these antagonists was reversed by PGE(2). By comparing NA dose-ratios in the presence of antagonist with dose-ratios in the presence of antagonists plus different doses of PGB(2), I showed 1hat the degree of reversal was related to the dose of PGE. For example, the NA dose - ratio for yohimbine (1.28 x 10(-6)M) was reduced from 26.6 + 0.9 to 1.7 + 0.1 when PGE(2) (2.8 x 10(-8) M)was included in the perfusion fluid with the antagonist. The reverse of antagonism was not due to a change in the binding characteristics of the α- adrenoceptor since pA(2) values for the antagonist were not significantly different (P<0.05) when PGS was included with the antagonists. Evidence is presented which suggests that reversal of antagonism involved utilization of internally bound calcium since reversal of antagonism occured even after the omission of Ca(2+) from the external medium. In this sense, the mechanism of reversal was different from that of potentiation. Furthermore, the degree of reversal (measured as-reversal factor) was quantitatively greater than would be the case if reversal was simply a reflection of the enhgresponsiveness of the vascular muscle to NA. In contrast to the "competitive” α- adrenoceptor antagonists, PGE(2) did not reverse the block of NA vasoconstriction caused by phenoxybenzamine (high doses); verapamil, cinnarizine or prazosin. All these agents caused blockade of NA that was not competitive in nature. Since none of the competitive α- adrenoceptor antagonists prevent prostaglandin formation; the point is made, that a prostaglandin can reverse NA blockade even if the blockade did not involve inhibition of prostaglandin synthesis.